INTEGRASI MODEL PROJECT BASED LEARNING DALAM SELF REGULATED LEARNING TERHADAP PENINGKATAN LITERASI LINGKUNGAN DI PERGURUAN TINGGI - Jaharudin, Jaharudin; In’am, Akhsanul; Setyaningrum, Rina Wahyu; Pantiwati, Yuni (Universitas Pendidikan Muhammadiyah Sorong, 2024)
This research aims to integrate the project based learning (PjBL) model in self regulated learning (SRL) in Environmental Knowledge courses at universities. This research uses a qualitative approach with a single case study method. The research subjects were students taking Environmental Knowledge courses. The research results show that the integration of the PjBL model in SRL can improve students' ability to understand concepts and improve critical and creative thinking skills. Apart from that, students can also develop the ability to work together and communicate in groups, which can also be implemented in the formal education sector in elementary, middle, high school and tertiary institutions.